2016
DOI: 10.17344/acsi.2015.1975
|View full text |Cite
|
Sign up to set email alerts
|

Vertex Degree Weighted Path Indices

Abstract: Vertex degree weighted path indices P N (a, b, ...), for example P 1 (a, b), P 2 (a, b, c), P 3 (a, b, c, d), and P 4 (a, b, c, d, e), are good topological indices for some of the physicochemical properties of octanes with |R| max up to 0.999. Mutually optimized combinations of them are even better, R (P 1 ..P 4 ) is in the worst tested case > 0.9. The best results are obtained in mutually optimized combinations of some of them with some of the elements of the Universal matrix, in the worst tested case R = 0.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…are the vertex degrees. 9 The vertex-degree vertex-distance weighted elements of the Universal matrix are defined as u ij (a ij , b ij , c ij ) = v i a ×v j b ×d ij c , where v i and v j are the vertex degrees and d ij c is the distance between the vertices i and j. 14 In the text, they are often presented in a shorthand form as PN and u ij , respectively.…”
Section: Definitions Data and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…are the vertex degrees. 9 The vertex-degree vertex-distance weighted elements of the Universal matrix are defined as u ij (a ij , b ij , c ij ) = v i a ×v j b ×d ij c , where v i and v j are the vertex degrees and d ij c is the distance between the vertices i and j. 14 In the text, they are often presented in a shorthand form as PN and u ij , respectively.…”
Section: Definitions Data and Methodsmentioning
confidence: 99%
“…The path indices 1,2 and the connectivity indices [5][6][7][8] were previously considered to be two different groups of indices. It has been, however, shown 9 that both groups of them are parts of the vertex-degree weighted path indices PN(a, b, ...). The mutually optimized combinations of vertex-degree weighted path indices gave rise in the case of 29 physicochemical properties of octanes to R (P1..P4) > 0.9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Branching degrees of octane isomers were not intended to represent a new index but to be only a quantitative illustration of the degree of branching of octane isomers as it is felt by a group of their physicochemical properties. Previous 12 results have shown that topological indices, which describe the »regular« sequence of octane isomers, are not good indices for physicochemical properties of octane isomers. This is reflected in Table 2 also for the branching degrees of octane isomers, where only the Pitzer's acentric factor ω exceeds the lower limit of usefulness of R = 0.99.…”
Section: Perdih : Introduction Of Branching Degrees Of Octane Isomersmentioning
confidence: 97%
“…Later 8 were presented »regular«, in part intuitively derived sequences of octane isomers of increasing branching, one of them being Oct < 2M7 < 3M7 < 4M7 < 3Et6 < 25M6 < 24M6 < 23M6 < 34M6 < 3Et2M5 < 22M6 < 33M6 < 3Et3M5 < 234M5 < 224M5 < 223M5 < 233M5 < 2233M4, as well as the indices derived from a simplified version of the Universal matrix giving rise to such »regu-lar« sequences of octane isomers. Such a »regular« sequence is observed among some of the indices [9][10][11][12] V(a, b, c) ≡ V wm (a, b, c) and V L (a, b, c) as well as among some of the vertex degree weighted path one indices.…”
Section: Introductionmentioning
confidence: 99%